A NOVEL NONPEPTIDE CGRP RECEPTOR ANTAGONIST, COMPOUND 1 (WO98/11128) IS A HIGH AFFINITY COMPETITIVE ANTAGONIST AT THE CGRP1 RECEPTOR IN HUMAN CORONARY ARTERIES. (2001) - Hasbak Hasbak, P. P.; Opgaard Opgaard, O. Saetrum O. Saetrum; Eskesen Eskesen, K. K.; Schifter Schifter, S. S.; Arendrup Arendrup, H. H.; Longmore Longmore, J. J.; Edvinsson Edvinsson, L. L.
Abstract : Functional CGRP and adrenomedullin receptors appear to consist of at least three different kinds of proteins: the calcitonin receptor-like receptor (CRLR), receptor-activity-modifying protein (RAMPs), and the receptor component protein (RCP) that couples the receptor to the cellular signal transduction pathway.